Switchgrass Growth and Forage Quality Trends Provide Insight for Management. Issue 1 (19th April 2018) - Sena, Kenton L.; Goff, Ben; Davis, David; Smith, S. Ray
Abstract : Core Ideas: Switchgrass forage quality declines predictably throughout season. Switchgrass biomass accumulates predictably during the season. Seasonal biomass and forage quality patterns may permit flexible management. Switchgrass ( Panicum virgatum ) has been identified as a valuable crop for biomass and liquid biofuels, as a viable summer forage for cattle, and as a dual‐use crop for both applications. The objective of this research was to evaluate trends throughout the growing season in biomass and forage quality of two switchgrass cultivars in central Kentucky over a 2‐yr period. Consistent with observed trends about these cultivars, Cave‐in‐Rock yielded moderate total biomass and had relatively good forage quality through early‐mid season growth. Alamo accumulated high total biomass, but demonstrated marginal forage suitability. This research produced trends predicting biomass and forage quality by accumulated growing degree days, and these trends will aid producers in managing switchgrass for biomass and/or forage utilization.